2006
DOI: 10.1007/bf02898145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β3-adrenergic receptor gene polymorphism on body weight change in middle-aged, overweight women

Abstract: Objectives: To examine the effects of β 3 -adrenergic receptor gene polymorphism on body weight change during a weight reduction program for middle-aged, overweight women with careful consideration of their energy intake and expenditure.Methods: Design: Intervention study of weight reduction for 12 weeks in a community setting. Subjects: Eighty overweight middle-aged women who completed the individualized lifestyle modification program. Measurements: β 3 -adrenergic receptor gene polymorphism was identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…In other words, the BMI reduction during an exercise-based intervention was not affected by the ADRB3 Trp64Arg polymorphism. Among our subjects, the frequency of the Arg allele was 19.3%, which is similar to frequencies (16.6-25.0%) reported among Japanese in other studies [22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In other words, the BMI reduction during an exercise-based intervention was not affected by the ADRB3 Trp64Arg polymorphism. Among our subjects, the frequency of the Arg allele was 19.3%, which is similar to frequencies (16.6-25.0%) reported among Japanese in other studies [22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 89%
“…Although the BMI had fallen by 0.8-0.9 kg/m 2 by the third month of our intervention, there is a possibility that a less stringent intervention, such as a 0.2 kg/m 2 of BMI reduction, may have revealed a difference between the Arg allele non-carriers and carriers. In their studies on Japanese obese females, Yoshida et al [22], Sakane et al [23], Kogure et al [24], and Lee et al [25] reported that Arg allele carriers had difficulty losing weight. The BMI reduction in these studies was larger, about 2 kg/m 2 in Arg allele non-carriers and 3 kg/m 2 in Arg allele carriers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the previously mentioned studies demonstrating no significant differences between ADRB3 rs4994 genotype after participating in a weight loss intervention [12,[43][44][45], some investigations have found significant differences between genotype [47][48][49]. Phares et al [47] conducted a six-month weight loss intervention within 70 apparently healthy, overweight (average BMI 28 kg/m 2 ), Caucasian men and women (29 men, 41 women), aged 50-75 years old.…”
Section: Adrb3 (Rs4994)mentioning
confidence: 97%